Development of Biocomposite Alginate-Cuttlebone-Gelatin 3D Printing Inks Designed for Scaffolds with Bone Regeneration Potential - Filis Curti; Andrada Serafim; Elena Olaret; Sorina Dinescu; Iuliana Samoila; Bogdan Stefan Vasile; Horia Iovu; Adriana Lungu; Izabela Cristina Stancu; Rodica Marinescu (Marine Drugs, 2022)
Fabrication of three-dimensional (3D) scaffolds using natural biomaterials introduces valuable opportunities in bone tissue reconstruction and regeneration. The current study aimed at the development of paste-like 3D printing inks with an extracellular matrix-inspired formulation based on marine materials: sodium alginate (SA), cuttlebone (CB), and fish gelatin (FG). Macroporous scaffolds with microporous biocomposite filaments were obtained by 3D printing combined with post-printing crosslinking. CB fragments were used for their potential to stimulate biomineralization. Alginate enhanced CB embedding within the polymer matrix as confirmed by scanning electron microscopy (ESEM) and micro-computer tomography (micro-CT) and improved the deformation under controlled compression as revealed by micro-CT. SA addition resulted in a modulation of the bulk and surface mechanical behavior, and lead to more elongated cell morphology as imaged by confocal microscopy and ESEM after the adhesion of MC3T3-E1 preosteoblasts at 48 h. Formation of a new mineral phase was detected on the scaffold’s surface after cell cultures. All the results were correlated with the scaffolds’ compositions. Overall, the study reveals the potential of the marine materials-containing inks to deliver 3D scaffolds with potential for bone regeneration applications.